THE EFFECT OF THIRD PARTY FUND, LDR AND OPERATIONAL COSTS ON OPERATIONAL INCOME ON ROA IN PUBLIC CREDIT BANK - Mertyani Sari Dewi (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
The purpose of this study was to determine the effect of Third Party Funds, Loan Debt Ratio and Operational Cost of Operating Income on Return On Assets in Rural Banks in Buleleng Regency. The type of data from this research is quantitative and qualitative data. Sources of data in this study are primary data and secondary data. The problem in this study is whether third- party funds affect the return on assets in rural banks in Buleleng regency, whether the loan debt ratio affects the return on assets in rural banks in Buleleng, whether operational costs of operating income affect the return on assets in rural banks in Buleleng regency and whether third-party funds, loan debt ratio and operating income operational costs affect the return on assets in rural banks in Buleleng regency. The results of this study are that third party funds have a negative and significant effect on return on assets in rural banks in Buleleng Regency, loan to debt ratio has a negative but not significant effect on return on assets in rural banks in Buleleng, operational costs of income operational has a negative and significant effect on return on assets in rural banks in Buleleng Regency and third party funds, loan to debt ratio, and operational costs of operating income have a significant effect on return on assets in rural banks in Buleleng Regency